Value Stream Mapping at Sahlgrenska University Hospital Understanding and Improving the Coordination Process of Breast Cancer Surgeries - Brigel, Vincent; Olsson, Cajsa (My University, 2018)
Sahlgrenska University Hospital (SU) is one of Sweden’s largest hospitals with a wide range of specialist treatments and research. Within the scope of surgery there are three primary care units, with one of them being Surgery Unit 33 (the surgery department). At the surgery department, patients diagnosed with breast cancer, malignant melanoma, endocrine disease or obesity are treated, with the largest share of them being breast cancer patients. At the surgery department, around 900 surgeries of breast cancer surgeries are performed each year. The need for breast cancer surgeries has grown throughout the years and combined with a broader range of surgical options and constrained resources it has become challenging to coordinate them. The surgery coordinators responsible for breast cancer surgeries have developed their own solutions over the years to handle the coordination process, which has made the process dependent on a person. In addition to that, the work environment has become stressful and there is a consensus regarding the need to gain an overview of the coordination process, identify potential problems and find ways to improve the process. The purpose of this thesis was thus to understand and document how the coordination process of breast cancer surgeries works today and develop improvements that can decrease the problems the process currently is faced with. To gain an overview of the process, a Value Stream Mapping was conducted where a current state map provided a visualization of the work flow along with detailed description for each step. In order to understand where potential problems arise with the process, this current state was analysed. The identified problem areas were divided into three areas; internal disturbances, external disturbances and uncertainties. Internal disturbances refer to the problems arising in the coordination process itself and hinders the steps described in the current state. External disturbances relate to the many different interruptions and issues that hinders the coordinators in their daily work. Uncertainties concerns the factors that affects the planning on a higher level and longer time horizon. In the development of improvement suggestions for the process, a future state map was developed. This map included a visualization of how the coordination process could flow and was followed by an elaboration on general improvements. In order to improve the process, main changes included the removal of the frequent controls of journals for defects which is not the coordinators responsibility, removal of unnecessary inventory steps creating motion and a proposal on a new way to coordinate patients by merging two activities when possible. Other general improvements for instance included to implement Poka-yoke to reduce defects and visualize information to reduce questions. There are multiple changes needed to make the coordination process more efficient. It should be noted that it is not enough to only improve the coordination process, but also a need to take on a long-term strategic approach when investigating how resources such as operating rooms should be allocated. Many factors and processes are connected and will be affected if one process is changed. Thus, change might be needed in several different processes in order to achieve long term differences. Crucial in order to achieve this is to communicate within the department and hospital wide, as well as striving to continuously improve the processes.
Keywords: Produktion; Transport; Grundläggande vetenskaper; Hållbar utveckling; Övrig industriell teknik och ekonomi; Production; Transport; Basic Sciences; Sustainable Development; Other industrial engineering and economics